The generations and gender survey: a cross-national longitudinal resource - Gauthier, Anne Hélène; Kong, Siyang; Grünwald, Olga; Bujard, Martin; Caporali, Arianna; Deimantas, Vytenis Juozas; Emery, Tom; Jablonski, Wojciech; Koops, Judith C; Rijken, Arieke; Schumann, Almut (European sociological review, 2025)
People's life trajectories and family dynamics have become increasingly complex, bringing shifts in fertility, gender equality, work-life balance, and economic stability. The scientific challenge is to capture these complexities and understand their causes and consequences. The Generations and Gender Survey (GGS) provides key insights into these developments, serving as a vital resource for researchers and policymakers.The GGS is a cross-national longitudinal survey collecting data on individuals aged 18 to 79 across topics such as union formation, fertility, household dynamics, work, well-being, and gender attitudes. Its key strengths include cross-national comparability, a panel design with prospective and retrospective data, large sample sizes, and multi-mode data collection. The GGS consists of two rounds: GGS-I, launched in the early 2000s in over 20 countries, established a foundation for comparative research, while GGS-II, started in 2020, builds on GGS-I with methodological innovations such as mixed-mode data collection and refreshed samples.This data brief provides an overview of the GGS, outlining its development, design, implementation, and key features. It also highlights the survey's contributions to demographic and social research, and explores the new research opportunities emerging with GGS-II.
Online erschienen: 23. August 2025
Gesehen am 04.02.2026